Representasi Budaya Jember Di Museum Tembakau - Ananda Ines Putri Winanti; Nur Intan Mutiara; Esha Ayu Triana Waskita Putri (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
The life of the people of Jember, which has long been inseparable from tobacco farming activities, sparked the birth of the idea of building a tobacco museum. This tobacco museum can be said to be a representation of how tobacco developed in the city of Jember. Several aspects contained in it also support the representation process. Starting from the beginning of the construction of the museum which was inspired by the habits of the people of Jember city, namely tobacco farming, the names of several agricultural tools were born from the language of the local community, even to the concept of the building which was interpreted as having similarities with one of the tools for tobacco production, namely the Atag warehouse. This research uses a representation theory perspective proposed by Stuart Hall. According to Hall, there are three approaches to the representation process consisting of reflective, intentional and constructionist approaches. The aim of this research is to find out how the representation process occurs in the tobacco museum. This type of research is qualitative research with an ethnographic approach. The results of the research show that there has been representation in the tobacco museum where the process involves various aspects contained in the museum itself.